2015
DOI: 10.1002/ejic.201500057
|View full text |Cite
|
Sign up to set email alerts
|

Room‐Temperature Hydrogenation of Citral Catalyzed by Palladium–Silver Nanocrystals Supported on SnO2

Abstract: We have developed two strategies to optimize Pd catalysts. On one hand, Ag was introduced into Pd and then they were applied to the selective hydrogenation of citral under mild conditions. The addition of metallic Ag could tune the selectivity of Pd and made it suitable for the selective hydrogenation of the conjugated double bond. The selectivity of citronellal increased from 0 (for Pd/C and Pd 0.7 Ag 0.3 /C) to 96 % (for Pd 0.4 Ag 0.6 /C) as the Ag content increased. On the other hand, the addition of SnO 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Generally, it has been observed that a high yield of menthol production via citral hydrogenation would possibly be produced with the use of selective, active, and recyclable bifunctional (metal–acid) catalysts with selective properties. Various catalytic-material-supported (metals), such as H-MCM-41, Al-MCM-41, H-Y zeolite, beta zeolite, activated carbon, Zr-zeolites, ionic liquid catalysts, nickel-supported metals [ 9 ], MOF-derived AgCo alloy nanoparticles [ 10 ], Pt/Sn [ 11 ], Ru-HY extrudates [ 12 ], Pt/SiO 2 [ 13 ] nano-composite catalysts [ 14 ], ruthenium nanoparticles [ 15 ], and SiO 2 -Al 2 O 3 , have been applied in citral hydrogenation reactions to obtain a higher yield of menthol [ 16 , 17 ]. Conversely, it has been observed that menthol selectivity would possibly be decreased due to the lack of active and selective catalyst designs that occur because of the formation of undesired/unrestrained hydrogenations, as well as cracking side reactions [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, it has been observed that a high yield of menthol production via citral hydrogenation would possibly be produced with the use of selective, active, and recyclable bifunctional (metal–acid) catalysts with selective properties. Various catalytic-material-supported (metals), such as H-MCM-41, Al-MCM-41, H-Y zeolite, beta zeolite, activated carbon, Zr-zeolites, ionic liquid catalysts, nickel-supported metals [ 9 ], MOF-derived AgCo alloy nanoparticles [ 10 ], Pt/Sn [ 11 ], Ru-HY extrudates [ 12 ], Pt/SiO 2 [ 13 ] nano-composite catalysts [ 14 ], ruthenium nanoparticles [ 15 ], and SiO 2 -Al 2 O 3 , have been applied in citral hydrogenation reactions to obtain a higher yield of menthol [ 16 , 17 ]. Conversely, it has been observed that menthol selectivity would possibly be decreased due to the lack of active and selective catalyst designs that occur because of the formation of undesired/unrestrained hydrogenations, as well as cracking side reactions [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Benefitting from their manifold compositions, valence states, and electron configurations, spinel compounds have attracted wide attention in magnetic, optical, electrical, and catalytic fields . In particular, for spinel nickel cobaltite (NiCo 2 O 4 ), the controllable composition, variable valence state, and easily constructed structure and morphology make it suitable for use as a catalyst or support for various catalytic reactions. Palladium-based materials have higher CC multibond activation capacity than other precious metals such as platinum, rhodium, and ruthenium. , And supported Pd nanoparticles are considered to be highly efficient catalysts for the hydrogenation of α,β-unsaturated carbonyl compounds. So NiCo 2 O 4 -supported Pd could be expected to show excellent selectivity and activity for the hydrogenation of α,β-unsaturated carbonyl compounds.…”
Section: Introductionmentioning
confidence: 99%
“…22−26 Palladium-based materials have higher CC multibond activation capacity than other precious metals such as platinum, rhodium, and ruthenium. 27,28 And supported Pd nanoparticles are considered to be highly efficient catalysts for the hydrogenation of α,βunsaturated carbonyl compounds. 29−33 So NiCo 2 O 4 -supported Pd could be expected to show excellent selectivity and activity for the hydrogenation of α,β-unsaturated carbonyl compounds.…”
Section: ■ Introductionmentioning
confidence: 99%